Letter from Max Bredig to Journal of Chemical Education - Bredig, Max Albert (1940)
Annotated letter from Max Bredig (1902-1977) to the editor of the Journal of Chemical Education. The letter was written in response to an article by Ernst A. Hauser (1896-1956), praising Wolfgang Ostwald (1883-1943). Bredig states that Ostwald was a member of the Nazi party and that his political affiliation should be acknowledged. Wolfgang Ostwald, the son of renowned chemist, Wilhelm Ostwald (1853-1932), became a full professor of chemistry at the University of Leipzig in 1935. In this letter to the editor, Max Bredig points out that anyone hired or promoted as a professor at the University of Leipzig at this time was considered to be closely connected to the Nazi party.
Keywords: Bredig, Georg, 1868-1944; Ostwald, Wilhelm, 1853-1932; Ostwald, Wolfgang, 1883-1943; Hauser, Ernst A. (Ernst Alfred), 1896-1956; Journal of chemical education; Chemists; Jewish Holocaust (1939-1945)